A Literature Review: The History of Psychological Impact of Illness amongst People with Leprosy (PwL) in Countries across the Globe - Pati Aji Achdiat; Eko Fuji Ariyanto; Michael Nobel Simanjuntak (Hindawi Limited, 2021)
Background. Leprosy is a chronic infectious disease for which effective therapy has been long since invented. Thus, the morbidity has been decreased as technology has advanced, but the permanent disability has continuously generated stigma for centuries. The stigma causes the emergence of a poor psychological impact on people with leprosy (PwL). These impacts make new PwL reluctant to get appropriate therapy for their initial symptoms and are, thus, troublesome in accomplishing the goals of the leprosy elimination program. The aim of this review is to provide the history of psychological impact amongst PwL in countries across the globe. Methods. This is a literature review study. A keyword-based search was conducted in digital libraries. Articles reporting on PwL's psychology and related issues, such as quality of life, opportunity of building a marriage, and getting hired, were included. The data were presented based on a leprosy history timeline with cutoff points, namely, the invention of promin (1941) and multidrug treatment (1970). Results. In total, 38 studies were included in this review. These studies showed that PwL's knowledge towards leprosy has been increasing; nevertheless, their attitude is still lacking. The emotional response was described by various negative feelings that had persistently occurred. These poor psychological impacts were followed by poor treatment-seeking behavior and resulted in low quality of life. Conclusions. From year to year, the PwL's knowledge about leprosy has been getting better; nevertheless, their attitude towards the disease is still poor. The emotional response, social participation, and quality of life of PwL are persistently poor due to the persistent stigma.